2016
DOI: 10.1002/jclp.22299
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Positive and Negative Emotional Experiences in Young Adults With Borderline Personality Disorder Symptoms

Abstract: Objectives Some researchers suggest that Borderline Personality Disorder (BPD) is characterized by elevated negative emotion; others argue that BPD involves both reduced positive and increased negative emotion. This study characterizes the emotional experiences of individuals with BPD symptoms in a combined university and community sample. Methods Participants (N=150) were completed a clinical interview assessing BPD symptoms and self-report measures of positive and negative emotion. A subset (n=106) complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(48 reference statements)
1
7
1
1
Order By: Relevance
“…However, the fact that PA accounted for variance in symptom severity, over and above NA, suggests that studying PA in BPD can contribute to further our understanding of this disorder. Our findings are in contrast with results from a previous study in which PA was not associated with BPD symptoms when NA was accounted for in analyses, leading the authors to conclude that BPD is primarily a disorder of elevated NA (Chu, Victor, & Klonsky, 2016). Unlike our study, this previous study examined the predictive effect of BPD symptoms on PA and NA and assessed symptoms only at baseline but similarly assessed PA and NA daily for a period of 2 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the fact that PA accounted for variance in symptom severity, over and above NA, suggests that studying PA in BPD can contribute to further our understanding of this disorder. Our findings are in contrast with results from a previous study in which PA was not associated with BPD symptoms when NA was accounted for in analyses, leading the authors to conclude that BPD is primarily a disorder of elevated NA (Chu, Victor, & Klonsky, 2016). Unlike our study, this previous study examined the predictive effect of BPD symptoms on PA and NA and assessed symptoms only at baseline but similarly assessed PA and NA daily for a period of 2 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…Although this might have biased our results, future research should consider evaluating more contexts and emotions to see whether the same effects are obtained. Finally, our studies focused on emotion goals, but given that individuals with BPD experience negative emotions with higher intensity (Chu et al ., ), future research should consider discriminating between what emotions they aim to feel and the intensity they wish to experience for each emotion. Furthermore, it should also consider exploring further whether people with BPD can discriminate between what they aim to feel and what is appropriate to feel in those contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Although Kuo and Linehan () suggested that individuals with BPD might exhibit emotional hyperreactivity, this has not been confirmed in other studies (Jacob et al ., ). Namely, different research studies have found that individuals with BPD do experience higher intensity only for negative emotions (Chu, Victor, & Klonsky, ). In fact, their experience and difficulties in the regulation of anger have been widely described in previous research (Koenigsberg et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NA is endemic to many affective disorders (Brown, Chorpita, & Barlow, 1998), findings suggest that those diagnosed with BPD and those who evidence BPD features report NA at higher levels than those with depressive and anxiety disorders (Fitzpatrick & Kuo, 2015;Jacob et al, 2009). Indeed, a large body of work associates BPD with intense, diffuse negative emotional states (Ebner-Priemer et al, 2007), and high levels of discrete negative emotions across laboratory (Gratz et al, 2010;Kuo & Linehan, 2009) and daily life settings (Chu, Victor, & Klonsky, 2016). Though the study of dispositional and momentary negative emotional arousal has been the mainstay of emotion dysregulation research, relatively less is known about the relationship between BPD features and the reactivity and recovery components of emotion dysregulation, and the processes that potentiate their occurrence in daily life.…”
Section: Introductionmentioning
confidence: 99%